Use of fecal and sawdust biochar as a new perfume delivery system. (25th September 2017) - Starkenmann, Christian; Niclass, Yvan; Beaussoubre, Pascal; Zimmermann, Janina; Cayeux, Isabelle; Chappuis, Charles Jean‐François; Fieber, Wolfgang
Abstract: Human fecal matter mixed with pine sawdust was heated at 200, 300, 400, 500, 600, or 650°C in the absence of oxygen to generate black solid residues called biochars. These biochars were subsequently evaluated as a perfume delivery system for air care. The performance of biochar was compared to that of cellulosic material, which is commonly used for the release of perfume into the air, and to that of active charcoal, which is used for air purification. A perfume model system consisting of alcohols, aldehydes, alkanes, and terpenes was loaded onto these solid materials. Results showed that the cellulosic material had a good release profile, but that the aldehydes oxidized to some extent, which generates a rancid smell if no antioxidant is added. On the other hand, active charcoal strongly absorbed all volatiles such that no perfume release occurred and no smell was perceived. The biochar heated at 200°C showed good release performance (long lasting) but some fecal off‐notes remained in the background. Biochar prepared at 300°C was the best material as a compromise between the release profile and the energy needed to produce the material. The goal of this work was to add value to biochar and in so doing empower toilet innovators, aid the circular economy, and propose a sustainable solution for malodor control. Abstract : Human fecal matter mixed with pine sawdust was heated in the absence of oxygen to generate black solid residues called biochars. Those were subsequently evaluated as a perfume delivery system for air care and compared to cellulose pads and active charcoal as benchmark systems. Biochar showed the best performance, in particular long lasting perfume release and chemical stability of the raw materials on the support.